Historical materialism and progress - Dolar, Robin (Retrospektive, 2025)
The paper addresses the concept of progress through an examination of di'erent paradigms in the natural and social sciences. By considering how progress relates to various theoretical frameworks, it analyzes the distinction between teleology and evolution; scientific attempts to reconstruct a theory of history; definitions of capitalism that imply continuous and discontinuous conceptions of historical development; and di'erent perspectives on premodern and modern institutions. The discussion concludes by outlining the implications these concepts hold for understanding modernity and progress. In doing so, the paper seeks to provide a nuanced account of how progress is portrayed in contemporary academic literature.
Keywords: capitalism; historical materialism; historični materializem; kapitalizem; modernity; modernost; napredek; New Institutional Economics; nova institucionalna ekonomija; progress